On Second-Order Sufficient Conditions in Constrained Nonsmooth Optimization (Communications in Mathematical Research, 2021)
In this paper, we establish a second-order sufficient condition for constrained optimization problems of a class of so called $ℓ$-stable functions in terms ofthe first-order and the second-order Dini type directional derivatives. The result extends the corresponding result of [D. Bednařík and K. Pastor, Math. Program. Ser.A, 113(2008), 283–298] to constrained optimization problems.